2010
DOI: 10.2166/wst.2010.419
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and use of Moringa oleifera seeds as biosorbent for removing metal ions from aqueous effluents

Abstract: Moringa oleifera seeds were investigated as a biosorbent for removing metal ions from aqueous effluents. The morphological characteristics as well as the chemical composition of M. oleifera seeds were evaluated using Fourier Transform Infrared (FT-IR) Spectroscopy, Thermogravimetric Analysis (TGA), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The FT-IR spectra showed the presence of lipids and protein components. Scanning electron micrographs showed that Moringa seeds have an adequate morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 0 publications
8
59
0
1
Order By: Relevance
“…The peak at 3000–2700 cm −1 showed the presence of the carboxylic acid (Bhutada et al, ). The peaks at 3010–3050 and 1600–1450 cm −1 showed the presence of benzene (CC) (Araújo et al, ). In the present study, there was no significant difference in the FTIR spectra between SBE and SCDE.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 3000–2700 cm −1 showed the presence of the carboxylic acid (Bhutada et al, ). The peaks at 3010–3050 and 1600–1450 cm −1 showed the presence of benzene (CC) (Araújo et al, ). In the present study, there was no significant difference in the FTIR spectra between SBE and SCDE.…”
Section: Resultsmentioning
confidence: 99%
“…According to Figure , it can be observed that the FTIR spectrum presented bands in an area of 3200–3500 cm −1 for albumin, globulin, and saline extract, and this band can be attributed to the presence of hydroxyl groups (OH), which are present in proteins and fatty acids . The bands at ∼2923 and ∼2852 cm −1 are attributed to symmetrical and asymmetrical elongation of the C‐H‐CH 2 , respectively, in fatty acids, and such groups are present in all analyzed coagulants. According to Paula et al, in the active principle of Moringa oleifera seeds, there are isothiocyanate groups (N = C = S), and these are characterized by absorption at 1238 cm −1 (C = S), which was demonstrated for all the coagulants analyzed in the present study.…”
Section: Resultsmentioning
confidence: 94%
“…Effective removal of azo and anthroquinonic dyes, and organic compounds viz., benzene, toluene, ethylbenzene, and cumene using seed extracts and fruits, respectively has also been demonstrated (Akhtar, Hasany, Bhanger, & Iqbal, ; Beltran & Snchez, ). Different parts of M. oleifera viz., seed powder for Cd +2 (Kituyi et al, ; Mataka, Sajidu, Masamba, & Mwatseteza, ; Sharma, Kumari, Srivastava, & Srivastava, ), Pb +2 and Cr +2 (Adhiambo et al, ); Zn +2 (Kituyi et al, ), As +3 and As +5 (Kumari, Sharma, Srivastava, & Srivastava, ); seeds for Ag +1 and Co +2 (Araujo et al, ); activated carbon from husk and pods for Pb +2 (Nadeem et al, ); activated carbon from wood for Cu +2 , Ni +2 , and Zn +2 (Kalavathy & Miranda, ); activated carbon from leaves for Cd +2 , Cu +2 , and Ni +2 (Reddy, Seshaiah, Reddy, & Lee, ); biomass for Zn +2 (Bhatti, Mumtaz, Hanif, & Nadeem, ); bark for Pb +2 (Reddy, Seshaiah, Reddy, Rao, & Wang, ); leaves for Pb +2 (Reddy, Harinath, Seshaiah, & Reddy, ); husk Cu +2 and Cd +2 (Garcia‐Fayos, Arnal, Piris, & Sancho, ) have been tested as biosorbents agents. However, seeds of different Moringa species could also be used as a low‐cost biosorbent for removal of heavy metals, that is, Cd +2 , Cr +2 , and Ni +2 from aqueous media (Mataka et al, ; Sharma, Kumari, Srivastava, & Srivastava, ).…”
Section: Resultsmentioning
confidence: 99%